2021
DOI: 10.1177/11206721211009450
|View full text |Cite
|
Sign up to set email alerts
|

Rhino-orbital mucormycosis during steroid therapy in COVID-19 patients: A case report

Abstract: Purpose: To report two cases of COVID-19 under treatment with a corticosteroid; in one case rhino-orbitocerebral mucormycosis and in another one rhino-orbital mucormycosis developed. Case presentation: A 40-year old woman and a 54-year old man with severe COVID-19 underwent corticosteroid therapy for immune-related lung injuries. The first case presented with a bilateral visual loss and complete ophthalmoplegia of the right eye. The second case presented with vision loss, proptosis, orbital inflammation, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
89
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(100 citation statements)
references
References 16 publications
2
89
0
Order By: Relevance
“…In a letter to the editor of 10 cases of orbital mucormycosis, Sarkar et al reported a mortality of 40% [ 24 ]. Multiple case reports were published and most of the survival was poor [ 24 , 25 ]. Quite surprisingly in a case series of 23 patients of CAM by Sharma et al, no death was reported [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a letter to the editor of 10 cases of orbital mucormycosis, Sarkar et al reported a mortality of 40% [ 24 ]. Multiple case reports were published and most of the survival was poor [ 24 , 25 ]. Quite surprisingly in a case series of 23 patients of CAM by Sharma et al, no death was reported [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of all the reports, 11 publications were from India [ 24 26 , 30 37 ]. The most commonly reported infection sites were rhino-orbital/rhino-cerebral mucormycosis[ 24 26 , 30 , 32 37 , 40 , 42 , 45 , 47 , 52 54 ]. Other presentations included pulmonary [ 31 , 41 , 43 , 44 , 49 , 51 , 55 ], cutaneous [ 46 ], disseminated [ 56 ] and gastrointestinal [ 48 ] diseases.…”
Section: Clinical Features and Managementmentioning
confidence: 99%
“…The reported organisms were Rhizopus spp. [ 24 , 31 , 36 , 41 44 , 47 , 49 , 51 , 55 ] and the others were reported as unspecified Mucorale [ 25 , 26 , 30 , 33 35 , 37 , 40 , 45 , 48 , 50 , 52 , 54 ]. The management of mucormycosis is usually difficult and requires urgent medical and surgical debridement while the choice of drug to treat mucormycosis is Amphotericin B [ 23 , 57 ] and Amphotericin was used in 23 of the included studies [ 24 26 , 30 37 , 40 44 , 46 , 47 , 49 – 54 ] and surgical debridement was reported in 20 of the included studies [ 24 26 , 30 , 32 37 , 40 , 44 47 , 50 – 54 ].…”
Section: Clinical Features and Managementmentioning
confidence: 99%
“…MRI is more sensitive than CT for detecting orbital and CNS involvement. 7 Based on the infected region, the imaging findings may include paranasal sinuses inflammation itself in early stages later patient may develop bony destruction and invasion to orbital tissues causing intraorbital tissue signal alteration with or without focal mass finally it invades cavernous sinus via blood stream reveals cavernous sinus filling defect suggestive of thrombus, intracranial focal mass. Patients suspecting mucormycosis should always go through diagnostic nasal endoscopy and/or surgical exploration functional endoscopic sinus surgery, with biopsy and KOH mount of the areas of suspected infection.…”
Section: Discussionmentioning
confidence: 99%